Fill in the table using the function rule y= 3x + 5
________________________________________
Replace each value of x in the expression
____________________________________
x= -4
y = 3* (-4)+5
= -12 +5
= -7
_______________
x= -2
y = 3* (-2)+5
= -6 +5
= -1
_____________
x= 0
y = 3* (0)+5
= 0 +5
= 5
_____________
x= 2
y = 3* (2)+5
= 6 +5
= 11
______________________________
Answer
_________________________
Can you see the updates?
Do you have any questions regarding the solution?
If you don’t need further explanation on this question, we can end the session.
I want to remind you this answer will always be saved in your profile. I’d really appreciate you letting me know how I did by rating our session after you exit. Thanks and have a great day!